A Hormonal Storm Behind the Heart: ACTH-Producing Pheochromocytoma Presenting with Acute Coronary Syndrome and Diabetic Ketoacidosis - Reesi, Ali Al; Alali, Ibrahim; Ghaithi, Salem Al (Journal of Diabetes and Endocrine Practice, 2025)
Clinical manifestations of pheochromocytoma can be highly variable and life-threatening, particularly affecting the endocrine and cardiovascular systems. We report an unusual case of adrenal pheochromocytoma.A 54-year-old woman with long-standing diabetes and prior cardiovascular events presented with episodic chest pain and labile blood glucose levels. Imaging revealed a left adrenal mass and biochemical studies confirmed excessive catecholamine and adrenocorticotropic hormone (ACTH) secretion, with failure of cortisol suppression. Adrenalectomy confirmed pheochromocytoma with ectopic ACTH production. Postoperatively, the patient achieved complete biochemical remission and glycemic stability on metformin monotherapy.This case highlights the diagnostic complexity of pheochromocytoma with atypical presentations. ACTH cosecretion can mimic Cushing's syndrome and precipitate metabolic crises such as diabetic ketoacidosis. Early recognition and surgical intervention are essential for improving clinical outcomes and achieving long-term stability.
Keywords: pheochromocytoma; ACTH secretion; diabetic ketoacidosis; acute coronary syndrome; adrenal tumor; endocrine disorders